Improved enhancement in CT angiography with reduced contrast media iodine concentrations at constant iodine dose. Issue 1 (December 2018) - Van Cauteren, Toon; Van Gompel, Gert; Nieboer, Koenraad; Willekens, Inneke; Evans, Paul; Macholl, Sven; Droogmans, Steven; de Mey, Johan; Buls, Nico
Abstract The study objective is to investigate the impact of a wide range of contrast media (CM) iodine concentrations on CT enhancement at constant total iodine dose (TID) and iodine delivery rate (IDR). Seven injection protocols, based on different iodine concentrations ranging from 120 to 370 mg I/mL, were assessed on 4 minipigs at a constant TID of 320 mg I/kg and IDR of 0.64 g I/s. Dynamic images were acquired on a clinical 64-slice MDCT scanner for 120 s with the abdominal aorta, vena cava inferior and liver parenchyma in the field-of-view. Maximal enhancement, time-to-peak and peak width were assessed. The enhancement curve characteristics were correlated with CM iodine concentration. In particular, CM with lower iodine concentrations yielded a significant increased maximal enhancement and peak width compared to the standard-of-care concentrations: e.g. in the aorta, 245 HU maximal enhancement and 9.2 s peak width with the 320 mg I/mL iodine concentration increased to 291 HU and 16.1 s with 160 mg I/mL. When maintaining a constant TID and IDR, by compensating injection rate and volume, injection of a CM with reduced iodine concentration results in a diagnostically beneficial higher maximal enhancement and longer enhancement peak duration.